Sites of violence : gender and conflict zones - Giles, Wenona Mary, 1949-; Hyndman, Jennifer (University of California Press, 2004)
Augmenting feminist analysis on conflict zones, this volume explores the gendered politics of ethno-nationalism 'honour-killings' in Iraq & Kurdistan, the civil war in Sudan & geographies of violence in Ghana, to investigate what happens when violence is invoked against people.
Keywords: Violence.; Political violence.; Social conflict.; Women -- Crimes against.; Sex role.; Sex differences.; Feminist theory.; Violence politique.; Conflits sociaux.; Femmes -- Crimes contre.; Rôle selon le sexe.; Différences entre sexes.; Théorie féministe.; violence.; terrorism.; sex role.; social conflict.; SOCIAL SCIENCE -- Violence in Society.; SOCIAL SCIENCE -- Gender Studies.; Feminist theory; Political violence; Sex differences; Sex role; Social conflict; Violence; Women -- Crimes against; Feminismus; Frau; Gewalt; Politik; Politischer Konflikt; Geweld.; Etnische conflicten.; Vrouwen.; Sekserol.; Aufsatzsammlung.